1999
DOI: 10.1063/1.370745
|View full text |Cite
|
Sign up to set email alerts
|

Strain profiles in overcritical (001) ZnSe/GaAs heteroepitaxial layers

Abstract: ZnSe layers of various thicknesses have been grown epitaxially on (001)-oriented GaAs substrates by metalorganic vapor phase epitaxy and studied by x-ray diffraction and Raman scattering. Consistent results have been found for the in-plane strains of both, ZnSe layers below and above the critical value of plastic relaxation. The experimental results are well described by strain profiles which are evaluated by an energy model and a geometrical model including the effects of strain and work hardening. The thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…Note that even the 5.4 mm thick ZnSe layer contains a residual compressive strain at its growth temperature of 550 K in agreement with Ref. [9].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Note that even the 5.4 mm thick ZnSe layer contains a residual compressive strain at its growth temperature of 550 K in agreement with Ref. [9].…”
Section: Resultssupporting
confidence: 89%
“…Figure 3c shows also the nonzero residual compressive strain present in the 5.4 mm thick ZnSe layer at growth temperature of 550 K in agreement with Ref. [9]. Thus, the direct interpretation of strains in several mm thick ZnSe layers as purely thermally induced seems to be at least doubtful.…”
Section: Resultssupporting
confidence: 84%
“…However, RHEED yields no information about the vertical lattice constant a Ќ , which yields strain due to lattice mismatch and differences in thermal expansion. 4 Strain must be controlled, for example, in order to achieve shifts of electronic band gaps 5 or to induce the formation of self-organized quantum dots, 6 but in many cases strain will be disadvantageous, because it gives rise to the formation of lattice defects upon relaxation, which deteriorate the optical 7,8 and transport 9 properties. Up to now, strain is measured ex situ by x-ray diffraction ͑XRD͒.…”
mentioning
confidence: 99%
“…These strains are relaxed by formation of structural defects like stacking faults and dislocations. Existing stacking faults and other defects near the interface, like the case of ZnSe grown on GaAs [1][2][3][4][5][6][7] are frequently the sources of new dislocations which propagate from the interface into the epitaxial epilayer [19] sometimes leading to internal micro-cracks.…”
Section: Properties Of the Samples After Pressure Treatmentmentioning
confidence: 99%
“…Several reports on ZnSe-based heterostructures have shown that formation of structural defects at the ZnSe/GaAs interface plays a crucial role in the degradation process [1][2][3][4][5][6][7]. Strains induced by the lattice mismatch between the substrate and the epilayer lead to creation of many crystal defects (point defects, dislocations, V-shape stacking faults etc) near the interface.…”
Section: Introductionmentioning
confidence: 99%